Implementasi IKM Berdasarkan PERMENPAN RB Nomor 14 Tahun 2017 Sebagai Wujud Pelayanan Prima - Ni Putu Dyah Erna Savitri; Arif Devi Dwipayana; Yusime Fitasari (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Law of the Republic of Indonesia No. 25 of 2004 mandates the Community Satisfaction Index (IKM) as a benchmark for assessing the quality of public services. UPT PKB Malang City which provides services in the field of Motorized Vehicle Testing, needs to measure IKM. The last evaluation in 2020 showed a